2021
DOI: 10.1021/acsbiomedchemau.1c00040
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Existing Oxidative Stress Creates a Docking-Ready Conformation of the SARS-CoV-2 Receptor-Binding Domain

Abstract: The redox-dependent changes on the binding between the receptor-binding domain of the severe acute respiratory syndrome-coronavirus-2 spike protein and the peptidase domain of the human cell surface receptor angiotensinconverting enzyme II were investigated by performing molecular dynamics simulations. The reduced states of the protein partners were generated in silico by converting the disulfides to thiols. The role of redox transformation on the protein−protein binding affinity was assessed from the time-evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 50 publications
1
35
0
Order By: Relevance
“…MD simulations and MM/PBSA calculations revealed that the formation of disulfide bonds, prevalent during oxidative stress, created a conformation more ready to bind to the receptor, which offered future clues for alternate therapeutic possibilities. 497 Similar work was also performed by Ghasemitarei et al 498 One interesting study performed MM/PBSA calculations to reveal the binding affinities of SARS-CoV-2 S protein to the ACE2s from different species. 499 , 500 This study showed that chimpanzees’ binding affinity was even higher than humans, cats, pangolin, dogs, and monkeys, and chimpanzees had a similar affinity to humans, which suggested some mammals were also vulnerable to SARS-CoV-2.…”
Section: Methods and Approachesmentioning
confidence: 72%
“…MD simulations and MM/PBSA calculations revealed that the formation of disulfide bonds, prevalent during oxidative stress, created a conformation more ready to bind to the receptor, which offered future clues for alternate therapeutic possibilities. 497 Similar work was also performed by Ghasemitarei et al 498 One interesting study performed MM/PBSA calculations to reveal the binding affinities of SARS-CoV-2 S protein to the ACE2s from different species. 499 , 500 This study showed that chimpanzees’ binding affinity was even higher than humans, cats, pangolin, dogs, and monkeys, and chimpanzees had a similar affinity to humans, which suggested some mammals were also vulnerable to SARS-CoV-2.…”
Section: Methods and Approachesmentioning
confidence: 72%
“…Therefore, the simulation data was analyzed to examine any alteration in the inter-residue interaction at the interface of the RBD and PD domain. Earlier MD simulation studies [ 17 , 18 ] reported several key residues at the interface. In particular, a recent study by Fossum et al [ 17 ] identified three distinct zones in WT (Table 3 ), where interacting residue clusters were observed to be essential in providing a tighter binding between the RBM to the ACE2.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier MD simulation studies [ 17 , 18 ] reported several key residues at the interface. In particular, a recent study by Fossum et al [ 17 ] identified three distinct zones in WT (Table 3 ), where interacting residue clusters were observed to be essential in providing a tighter binding between the RBM to the ACE2. As shown in Table 3 , the left zone consists of two aromatic–aromatic interactions, namely, Y489(OH)···F28(N) and Y489(OH)···Y83(OH).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations